Answer

Verified

410.1k+ views

**Hint:**Now we know that the equation of a circle with center (h, k) and radius r is given by the ${{\left( x-h \right)}^{2}}+{{\left( y-k \right)}^{2}}={{r}^{2}}$ . Now we know the center and radius of the circle hence by substituting the value of h, k and r we will get the equation of the required circle.

**Complete step by step answer:**

Now we are given that the center and radius of the circle.

Let us first understand the meaning of the equation of circle.

Equation of a circle is a general equation of all the points (x, y) on the circle.

Now a circle is formed by plotting all the points which are equidistant from one point which is center.

Now equation of circle with center as origin is given by ${{x}^{2}}+{{y}^{2}}={{r}^{2}}$ where r is the radius of the circle.

Now if the circle has center (h, k) is the center of the circle then the equation of circle is given by ${{\left( x-h \right)}^{2}}+{{\left( y-k \right)}^{2}}={{r}^{2}}$ .

Now let us find the equation of the circle with center (0, 2) and radius 2.

Hence here we have h = 0, k = 2 and r = 2.

Hence the equation of the circle is,

$\Rightarrow {{x}^{2}}+{{\left( y-2 \right)}^{2}}={{2}^{2}}$

Now we know that ${{\left( a-b \right)}^{2}}={{a}^{2}}-2ab+{{b}^{2}}$

$\begin{align}

& \Rightarrow {{x}^{2}}+{{y}^{2}}-2y+4=4 \\

& \Rightarrow {{x}^{2}}+{{y}^{2}}-2y=0 \\

\end{align}$

Hence the equation of the circle is ${{x}^{2}}+{{y}^{2}}-2y=0$

Now consider the circle with center (-2, 3) and radius 4.

Here h = -2, k = 3 and r = 4.

Hence the equation of the circle is

$\Rightarrow {{\left( x-\left( -2 \right) \right)}^{2}}+{{\left( y-3 \right)}^{2}}={{\left( 4 \right)}^{2}}$

Now we know that ${{\left( a\pm b \right)}^{2}}={{a}^{2}}\pm 2ab+{{b}^{2}}$

$\begin{align}

& \Rightarrow {{x}^{2}}+2x+4+{{y}^{2}}-6y+9=16 \\

& \Rightarrow {{x}^{2}}+{{y}^{2}}+2x-6y-7=0 \\

\end{align}$

Hence the equation of the circle is ${{x}^{2}}+{{y}^{2}}+2x-6y-7=0$ .

**Note:**Now note that the general equation of circle is ${{x}^{2}}+{{y}^{2}}+2gx+2fy+c=0$ where (-g, -f) is the center of the circle and ${{g}^{2}}+{{f}^{2}}-c$ is the radius of the circle. Hence the circle is real only if the value of ${{g}^{2}}+{{f}^{2}}>c$ . In other cases the circle is a point or imaginary circle.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

How do you graph the function fx 4x class 9 maths CBSE

Difference Between Plant Cell and Animal Cell

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

What organs are located on the left side of your body class 11 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE